The Development of Zeolite as Potential Natural Catalyst : The Development of Zeolite as Potential Natural Catalyst - Dongoran, Junita; Sulistiawati, Putri; Simangunsong, Sri Yulandari; Paksi, Pandu Gizta Rapi; Pasaribu, Marvin Horale (Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Palangka Raya, 2021)
Zeolite is a hydrated aluminosilicate mineral (solid) in which silicate ions (SiO44-) and tetrahedral alumina (AlO45-) combine to form a porous/hollow and negatively charged crystal structure. Natural zeolite can be isolated from several sources, such as volcanic ash, sand, rocks, and rice husks, to industrial organic waste. Zeolite catalysts can be synthesized through various methods such as sol-gel, hydrothermal, ionothermal, and alkaline fusion. The purpose of modifying zeolite catalyst material is to improve its catalytic capabilities and physical and chemical properties, which can be done by various methods, including sol-gel, hydrothermal, ionothermal, and alkaline fusion. The use of zeolite-based catalysts and their derivatives has been widely used in various chemical reactions and industries such as isomerization processes, molecular cracking, to the manufacture of biodiesel. The conclusion is that zeolite is a widely developed material because of its abundant quantity in nature, and it is relatively cheaper and can be modified so that it can be used in various chemical reactions.